Productivity Investigation within the ERP System - Kujawa, Anna; Legutko, Stanislaw (Manufacturing Technology Journal, 2012)
The paper presents utilization of class ERP system for examination, analysis and updating of production standards. The investigation has been performed in a medium size enterprise manufacturing products of steel strip and sheet. It has been shown that everyday reporting of production in the ERP class system makes it possible to examine the individual products in respect of the production time and becomes a basis of verification of the standards imposed by the master firm. Continuation of the reexamination after verification of standards will most probably initiate introduction of piecework wage system.
Keywords: ERP system; productivity